A Multi-Group Structural Analysis of Digital Banking Adoption Determinants Across Generational Cohorts in Indonesia - Tribuana, Dhimas; Narimawati, Umi; Syafei, M. Yani (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study investigates factors affecting Digital Banking Adoption (DBA) across generations in Indonesia, focusing on performance expectancy, effort expectancy, social influence, facilitating conditions, and trust. Employing a cross-sectional design, the study collected data through a structured questionnaire administered to 360 respondents, selected through purposive and clustering sampling, from major cities including Jakarta, Bandung, Surabaya, and others. Structural Equation Modelling (SEM) and Multi-Group Analysis were applied to test hypotheses and assess generational differences in DBA. Findings reveal that performance expectancy, facilitating conditions, and trust significantly influence DBA, with notable differences across generations: Baby Boomers prioritize facilitating conditions, Generation X emphasizes performance expectancy, and Generation Y values both performance and effort expectancy. Generation Z, despite being tech-savvy, benefits from enhanced support structures for improved banking experiences. These results highlight the importance of tailored, generation-specific strategies in digital banking, providing valuable insights for service providers aiming to enhance user experience and adoption across demographic groups.